Tetramethoxyluteolin for the Treatment of Neurodegenerative Diseases - Theoharides, Theoharis C.; Tsilioni, Irene (Current Topics in Medicinal Chemistry, 2018)
Background: Most neurodegenerative and other brain disorders, especially Myalgic encephalomyelitis/ chronic fatigue syndrome (ME/CFS) and autism spectrum disorder (ASD) continue to elude objective biomarkers and effective treatments. Increasing evidence indicates that such diseases involve focal inflammation of the brain. Objective: To review the role of cytokine-neuropeptide interactions in the pathogenesis of inflammation of the brain and the beneficial role of natural flavonoids. Methods: Medline search was conducted (2000-2017) for articles using the terms allergy, amygdala, atopy, autism, brain, chemokines, cytokines, hypothalamus, immunity, inflammation, mast cells, microglia, neurotensin, peptides, substance P, and TNF. Results: Neuropeptides and cytokine stimulation of mast cells and microglia can result in focal inflammation in the hypothalamus and amygdala, thus explaining most of the symptoms at least in ME/CFS and ASD. Some of the triggers may be corticotropin-releasing hormone (CRH), neurotensin (NT), and substance P (SP), which have synergistic action on IL-33. The natural flavonoids luteolin and tetramethoxyluteolin inhibit these processes and have neuroprotective actions. Tetramethoxyluteolin is also more metabolically stable and has greater oral absorption. Conclusion: Inhibition of inflammatory processes unique to the brain with intranasal formulations of tetramethoxyluteolin could provide new possibilities for the understanding and treatment of neurodegenerative diseases.
Keywords: Inflammation